Palaeontological surveys in Central Sumatra and Bangka - Louys, Julien; Zaim, Yahdi; Rizal, Yan; Price, Gilbert J.; Aswan, Aswan; Puspaningrum, Mika Rizki; Smith, Holly; Hascaryo, Agus Tri (Ikatan Ahli Geologi Indonesia, 2021)
We report on results from surveys undertaken in Sumatra during 2018 and 2019. The surveys had three objectives: (1) to examine, sample, and record the extensive Quaternary fossil deposits from caves in West Sumatra; (2) determine the potential for fluvial deposits in Riau and Jambi provinces; and (3) relocate the fossil proboscidean remains reported from Bangka Island. Our surveys produced several significant results. We mapped three important Padang Highland caves, Ngalau Lida Ajer, Ngalau Sampit, and Ngalau Gupin, locating and sampling the main fossil deposits in each, as well as recording additional caves in the region. Our surveys of the fluvial systems in central-west Sumatra did not reveal any vertebrate Pleistocene deposits but did yield Mio-Pliocene trace fossils. Finally, we relocated elephant fossils from Bangka, but no in situ vertebrate remains could be found. These finds add important new data to the geological history of Sumatra.